2015
DOI: 10.1002/cncr.29499
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 60 levels in tissue and circulating exosomes in human large bowel cancer before and after ablative surgery

Abstract: BACKGROUND Heat shock protein 60 (Hsp60) is a chaperonin involved in tumorigenesis, but its participation in tumor development and progression is not well understood and its value as a tumor biomarker has not been fully elucidated. In the current study, the authors presented evidence supporting the theory that Hsp60 has potential as a biomarker as well as a therapeutic target in patients with large bowel cancer. METHODS The authors studied a population of 97 subjects, including patients and controls. Immunomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 38 publications
6
118
1
2
Order By: Relevance
“…Frequently, the immunopositivity for Hsp60, in cancerous tissue or circulating cancer cells, correlates with a poor prognosis [49,[51][52][53]. In contrast to these findings, we previously found that the loss of Hsp60 immunopositivity can be related to development and progression of bronchial cancer [54], which reflects the variety of roles that Hsp60 can play.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Frequently, the immunopositivity for Hsp60, in cancerous tissue or circulating cancer cells, correlates with a poor prognosis [49,[51][52][53]. In contrast to these findings, we previously found that the loss of Hsp60 immunopositivity can be related to development and progression of bronchial cancer [54], which reflects the variety of roles that Hsp60 can play.…”
Section: Discussioncontrasting
confidence: 59%
“…Various data support the hypothesis that Hsp60 favors carcinogenesis and show a close correlation between high levels of Hsp60 and different types of cancer, thus the immunopositivity for Hsp60 can be considered a biomarker useful for the diagnosis and monitoring these types of malignancies [33,[49][50]. Frequently, the immunopositivity for Hsp60, in cancerous tissue or circulating cancer cells, correlates with a poor prognosis [49,[51][52][53].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Because of its presence in tumor cells but not in healthy cells, HSP60-exosomes seem to be also interesting biomarkers in cancer, at least for large bowel cancer diagnosis. 132 …”
Section: Hsp-exosomes In Cancer Diagnosismentioning
confidence: 99%
“…Hsp60 may influence tumor progression as suggested by its accumulation in the cytosol and plasma membrane of cancerous cells, reaching the extracellular space via secretory vesicles that in turn can modulate (induce, or inhibit?) anti-tumor immune responses [50][51][52]. Hyperacetylation of Hsp60 in osteosarcoma cells is associated with the anticancer activity of geldanamycin and Hsp60 nitration is associated with the anti-tumor action of the histone deacetylase inhibitor SAHA [53,54].…”
Section: Hsp60mentioning
confidence: 99%